Pendidikan Lingkungan Hidup Melalui Praktik Kreasi Limbah Kertas Bagi Siswa Di SMP Negeri 16 Surabaya - Pandu Rudy Widyatama; Elok Kinanti; Elsa Amalia Risky; Lailatul Hilmiyah; Ita Dwi Lestari; Muhammad Syaifudin; Maya Mustika Kartika Sari (Lembaga Einstein College (LEC), 2024)
In schools, paper waste is a serious problem because high usage for assignments, duplication of materials, and administration is not balanced with effective waste management, so waste paper is often thrown away without being recycled, leading to waste accumulation and negative impacts on the environment. To overcome this, activities with a service learning (SL) approach are carried out, integrating student learning with community service. This approach not only allows students to apply the knowledge gained in the classroom, but also develops social skills, empathy, and responsibility. This activity went through the stages of problem identification, planning, service implementation, reflection, demonstration, evaluation, and sustainable development, attended by 25 students of SMP Negeri 16 Surabaya and supported by the Surabaya City Environmental Agency, as well as PPG students of the State University of Surabaya. The result was the creation of a 3-dimensional map of Indonesia's islands from paper waste, which showed good enthusiasm and student participation.